Stress and sleep: Results from the Hispanic Community Health Study/Study of Latinos Sociocultural Ancillary Study. (December 2017) - Alcántara, Carmela; Patel, Sanjay R.; Carnethon, Mercedes; Castañeda, Sheila F.; Isasi, Carmen R.; Davis, Sonia; Ramos, Alberto R.; Arredondo, Elva; Redline, Susan; Zee, Phyllis C.; Gallo, Linda C.
Abstract: Hispanics/Latinos face specific sociocultural stressors associated with their marginalized status in the United States. While stress is known to cause poor sleep, the differential effects of the specific stressors faced by Hispanics/Latinos have not been evaluated. Using cross-sectional data from the Hispanic Community Health Study/Study of Latinos Sociocultural Ancillary Study, we conducted weighted generalized linear models to evaluate the associations of acculturation stress, ethnic discrimination, and chronic moderate/severe stress with self-reported sleep outcomes (insomnia symptoms, daytime sleepiness, sleep duration) in individual and aggregate models adjusted for site, socio-demographics, behavioral, and medical conditions. Participants included 5313 Hispanic/Latino adults; 43.5% ≥ age 45, 54.8% female, and 22.0% US-born. Chronic moderate/severe stress, ethnic discrimination, and acculturation stress were each positively associated with sleep. In the adjusted aggregate model, only chronic moderate/severe stress was associated with insomnia symptoms (exp(b) = 1.07 for each additional stressor, 95% CI = 1.05, 1.09). Both acculturation stress (exp(b) = 1.05 for each additional SD, 95% CI = 1.02, 1.10) and ethnic discrimination (exp(b) = 1.05 for each additional SD, 95% CI = 1.01, 1.08) were associated with daytime sleepiness. Each SD increase in ethnic discrimination related to a 16% and 13% increased prevalence of short (< 7 h) (RRR = 1.16, 95% CI = 1.02, 1.31) and long sleep duration (> 9 h) (RRR = 1.13, 95% CI = 1.00, 1.27), respectively. These associations were consistent across sex. Acculturation stress and ethnic discrimination are associated with poor sleep in Hispanics/Latinos. Future research should explore whether behavioral sleep interventions minimize the impact of sociocultural stressors on sleep. Highlights: Latina/os face unique stressors associated with their marginalized status in the USA. We explored the association of sociocultural stressors with Latina/o sleep. Acculturation stress and ethnic discrimination were associated with daytime sleepiness. Only chronic psychosocial stress was associated with insomnia symptoms. Ethnic discrimination was associated with both short and long sleep duration.